Investigation of oxide layer on CdTe film surface and its effect on the device performance. (December 2015) - Jun-feng, Han; Liu, Xiao; Li-mei, Cha; Hamon, Jonathan; Besland, M.P.
Abstract: In this work, the chemical evolution of CdTe crystal and thin film under air exposure was investigated by X-ray Photoelectron Spectroscopy (XPS). In particular, the analysis of Te 3d core level allowed us to characterize the surface oxidation. Indeed, in both cases and after a short air exposure, the Te 3d peaks exhibited clearly two components corresponding to Te–Cd and Te–O, i.e. bulk CdTe and native oxide. The later one was used to estimate an equivalent oxide layer thickness. Only a weak oxide amount could be observed on both fresh surfaces, whereas after two days of air exposure, the native oxide thickness was estimated to 2.2 nm and 0.9 nm for CdTe crystal and thin film respectively. For a longer exposition time of one month, the oxide layer thickness increased in both cases up to 7.2 and 5.9 nm, for CdTe crystal and thin film respectively. Even, if the oxidation kinetic appeared slower in the case of CdTe thin film, such insulating oxide layer formation at CdTe surface under air exposure might have negative effect on the ohmic back contact formation and further electrical characteristics of solar cells. Next to this study, aged CdTe samples were submitted to a chemical etching after several days of air exposure and before solar cell fabrication. It appeared that solar cell based on 'aged CdTe layer' after etching exhibit electrical performances similar to those obtained with a freshly elaborated CdTe device. Therefore, CdTe chemical etching appears as an effective way to remove the surface oxide layer and retrieve good cell performances. As a result, it is possible to store CdTe films for long duration before solar cells fabrication.